Autonomic regulation of the heart and arrhythmogenesis in trained breath-hold divers. Issue 3 (4th March 2021) - Costalat, Guillaume; Godin, Benedicte; Balmain, Bryce N.; Moreau, Clara; Brotherton, Emily; Billaut, Francois; Lemaitre, Frederic
Abstract : Breath-hold divers are known to develop cardiac autonomic changes and brady-arrthymias during prolonged breath-holding (BH). The effects of BH-induced hypoxemia were investigated upon both cardiac autonomic status and arrhythmogenesis by comparing breath-hold divers (BHDs) to non-divers (NDs). Eighteen participants (9 BHDs, 9 NDs) performed a maximal voluntary BH with face immersion. BHDs were asked to perform an additional BH at water surface to increase the degree of hypoxemia. Beat-to-beat changes in heart rate (HR), short-term fractal scaling exponent (DFAα1), the number of arrhythmic events [premature ventricular contractions (PVCs), premature atrial contractions (PACs)] and peripheral oxygen saturation (SpO2 ) were recorded during and immediately following BH. The corrected QT-intervals (QTc) were analyzed pre- and post-acute BH. A regression-based model was used to split BH into a normoxic (NX) and a hypoxemic phase (HX). During the HX phase of BH, BHDs showed a progressive decrease in DFAα1 during BH with face immersion ( p  < 0.01) and BH with whole-body immersion ( p  < 0.01) whereas NDs did not ( p  > 0.05). In addition, BHDs had more arrhythmic events during the HX of BH with whole-body immersion when compared to the corresponding NX phase (5.9 ± 6.7 vs 0.4 ± 1.3; p  < 0.05; respectively). The number of PVCs was negatively correlated with SpO2 during BH with whole-body immersion ( r  = −0.72; p  < 0.05). The hypoxemic stage of voluntary BH is concomitant with significant cardiac autonomic changes toward a synergistic sympathetic and parasympathetic stimulation. Co-activation led ultimately to increased bradycardic response and cardiac electrophysiological disturbances.